A Comparison of Manipulative Use on Mathematics Efficiency in Elementary Students With Autism Spectrum Disorder. Issue 4 (December 2020) - Bassette, Laura; Bouck, Emily; Shurr, Jordan; Park, Jiyoon; Cremeans, McKenzie; Rork, Emma; Miller, Kelsey; Geiser, Sarah
Manipulatives are a commonly used intervention that provide visual instruction known to promote mathematical learning; however, the impact on students with autism spectrum disorder (ASD) is less understood. Improving mathematical procedural understanding is important for students with ASD given these skills can help increase access to more advanced mathematics and future opportunities (e.g., postsecondary education). This study expanded upon previous research and compared the ability of students with ASD to solve mathematical problems when using concrete and app-based manipulatives. A single-case alternating treatment design was used to explore differences in steps completed independently per minute (i.e., efficiency) and accuracy when using both types of manipulatives. Two participants were more efficient when using the app-based manipulative while one was more efficient with the concrete manipulative. Similar to previous research, all participants indicated they preferred the app-based condition. Limitations and future research are included.